Social Intelligence Moral Disengagement and Rule Breaking Behavior in University Male Students - Anfal Umar Hayyat; Masooma Rasheed (Research Journal of Psychology, 2025)
The current study is to investigate male university students' "moral disengagement", "social intelligence", and rule-breaking conduct. It is predicted that among male university students, there will probably be a substantial correlation between moral disengagement and social intelligence and rule-breaking conduct. Among university students, rule-breaking behavior will be favorably predicted by moral disengagement. The study involved 200 university male students and examined how moral disengagement and social intelligence relate to rule-breaking behavior. Using established assessment tools and statistical methods (correlation and regression analysis), the results showed a significant relationship among all three variables. Specifically, moral disengagement was found to be an accurate predictor of disobedient behavior. "Moral disengagement" will positively predict rule-breaking conduct among college students. The sample consists of two hundred adolescents currently enrolled in higher education. Data was gathered using evaluation instruments such the Social Intelligence Scale (SIS), created by Chadha and Ganesan in 1986, the 32-item "Moral Disengagement Scale" (MDS), created by Albert Bandura, and the Rule-breaking Behavior Scale. Linear regression analysis is used to investigate predictive associations, while "Pearson Product-Moment Correlation" are utilized to analyze the relationship between variables. The results showed that among male university students, social intelligence, moral disengagement, and rule-breaking conduct are significantly correlated. Additionally, it showed that among male university students, social intelligence, moral disengagement, and rule-breaking conduct are significantly correlated in male students.